Impact of oligoether chain lengths on the relaxation processes in poly(oligo(ethylene glycol) methyl ether methacrylate) networks that are synthesized by radiation-induced crosslinking polymerization. (May 2020) - Czaderna-Lekka, Anna; Piechocki, Krzysztof; Kozanecki, Marcin; Okrasa, Lidia
Abstract: The molecular mobility in poly(oligo(ethylene glycol) methyl ether methacrylate) (POEGMA) networks with varying side chain lengths ( n = 2–19 oxyethylene groups), which are synthetized by radiation-induced crosslinking polymerization, has been investigated by dielectric spectroscopy. A complete relaxation map for these materials with four processes was created for the first time. At higher temperatures, α relaxation corresponding to the dynamic glass transition and α' relaxation, which was likely correlated with sub-Rouse processes, were found. Below the dynamic glass transition, two Arrhenius-type processes were distinguished: the γ -process, which was assigned to the end (methoxy-) group; and weak β -relaxation, which was dependent on the oligoether chain length and was related to side chain movements. The fragility index for all of the POEGMA networks proves that these are strong glass-forming materials. In the partially crystalline samples with n  > 7, the relaxation processes are strongly disturbed by cold crystallization and melting. Graphical abstract: Image 1 Highlights: Molecular mobility in POEGMAs with various side chain lengths was analyzed. DRS was used to examined dried POEGMAs networks produced by RI-CP. Complex relaxation map with four processes was given for the first time. Two patterns of behavior may be distinguished – amorphous and semi-crystalline networks.